Respostas
respondido por:
41
a1 = 1
r = 2π
===
a2 = a1 + r
a2 = 1 + 2π
a3 = a2 + r
a3 = (1 + 2π) + 2π
a3 = 1 + 4π
a4 = a3 + r
a4 = (1 + 4π) + 2π
a4 = 1 + 6π
a5 = a4 + r
a5 = (1 + 6π) + 2π
a5 = 1 + 8π
===
PA = (1 , 1 + 2π, 1 + 4π, 1 + 6π, 1 + 8π)
r = 2π
===
a2 = a1 + r
a2 = 1 + 2π
a3 = a2 + r
a3 = (1 + 2π) + 2π
a3 = 1 + 4π
a4 = a3 + r
a4 = (1 + 4π) + 2π
a4 = 1 + 6π
a5 = a4 + r
a5 = (1 + 6π) + 2π
a5 = 1 + 8π
===
PA = (1 , 1 + 2π, 1 + 4π, 1 + 6π, 1 + 8π)
Anônimo:
obrigada
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás